2009
DOI: 10.1080/02640410802448764
|View full text |Cite
|
Sign up to set email alerts
|

Analogy versus explicit learning of a modified basketball shooting task: Performance and kinematic outcomes

Abstract: The effects of differential instructional sets on motor skill acquisition were investigated using performance outcome and kinematic measures. Participants were provided with a single analogical instruction (analogy learning), a set of eight explicit (technical) instructions (explicit learning), or were not instructed (control). During a learning phase, participants (n=9 for each condition) performed a modified basketball shooting task over 3 days (160 trials per day). On the fourth day, participants performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
166
3
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(185 citation statements)
references
References 34 publications
6
166
3
10
Order By: Relevance
“…Analogy versus explicit learning has predominantly been studied in table tennis. Recently Lam et al [25] investigated this subject in a modified basketball shooting task. In a dual task transfer test performance decrements were shown for explicit and control conditions, but not for the analogy learning group.…”
Section: Self-focus Explanations For Choking In Sensorimotor Skillsmentioning
confidence: 99%
“…Analogy versus explicit learning has predominantly been studied in table tennis. Recently Lam et al [25] investigated this subject in a modified basketball shooting task. In a dual task transfer test performance decrements were shown for explicit and control conditions, but not for the analogy learning group.…”
Section: Self-focus Explanations For Choking In Sensorimotor Skillsmentioning
confidence: 99%
“…To make statements about long-term effects within rehabilitation it may be desirable for future studies to include even longer follow up periods (> 3 months). Lastly, a verbal protocol will be assessed because it is hypothesised that participants within the implicit learning group will report fewer explicit rules than the control group, which would be in line with the findings of earlier studies 23,24 . Even though, the starting point of the explicit intervention is to use many verbal explicit instructions and provide more details on the motor performance, the exact number of explicit rules will be tailored to the ability of the patient to process these rules.…”
Section: Implicit Motor Learningmentioning
confidence: 62%
“…A good example was presented by Lam and colleagues 23 . They used the analogy instruction "Shoot as if you are trying to put cookies into a cookie jar on a high shelf" to teach basketball players to impart backspin on the basketball.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings had also been demonstrated by Liao and Masters (2001), who found that learners taught via metaphorical descriptions were not negatively affected by a stress intervention (i.e., via ego threatening feedback), or thought suppression techniques when compared with an explicit learning group. Further contemporary research (e.g., Lam, Maxwell, & Masters, 2009) has suggested that individuals taught via analogy / metaphor use more implicit or unconscious modes of movement control than those taught via explicit instruction. Finally, Jones (2003), advised that using practitioner or coach generated metaphors could be adopted as a literary technique to encourage athletes to identify alternative ways of viewing and dealing with situations.…”
mentioning
confidence: 99%